Grassroots diplomacy between Lesotho and South Africa: the district liaison committees - Moeletsi, Motheba Gwendoline (Rhodes University, Faculty of Humanities, Department of Political Studies, 2000)
Cross-border conflicts on the African continent have increased tremendously in the post-colonial years. The widespread border conflicts on the African continent have been attributed to the arbitrariness with which Africa's national boundaries were drawn during the colonial period. The colonial boundaries have left the doors open for perpetual conflicts among African states. This thesis proposes to investigate the prospects of grassroots diplomacy as an option of dealing with border conflicts with specific reference to the case of Lesotho/South Africa border relations. This is done by critically evaluating the role the District Liaison Committees (DLCs) have played in border relations between Lesotho and South Africa. The Lesotho and South African governments have institutionalised the resolution of border conflicts at grassroots level through the establishment of the DLCs. The DLCs consists of representatives of border communities in Lesotho and South Africa. The paper introduces a not so familiar concept of involving people at grassroots levels in the conducting of diplomacy between the two neighbouring countries. The central issue implicit in this paper is that grassroots diplomacy is succeeding in the case of Lesotho and South Africa. The DLCs have managed to reduce tension between the two countries along the borders which had existed over a long period of time, thereby, relieving the central governments of some of their duties. The thesis contents that high level conventional diplomacy is not always the answer to cross-border conflicts. The example of Lesotho and South Africa could be followed by other African countries in similar situations.
Keywords: Lesotho -- Foreign relations -- South Africa; South Africa -- Foreign relations -- Lesotho; Africa -- Foreign relations -- 1960-; Africa -- Politics and government -- 1960-